Application of UV-resin in the fabrication of iris button to improve occular prosthetic aesthetic - Steven Tiopan; Ariyani; Haslinda Z. Tamin (Indonesian Journal of Prosthodontic, 2023)
Background: One of the success criteria in occular prosthesis is providing a prosthetic that is similar with the natural eye. Several methods for creating artificial iris are the use of iris from stock eyes, photo paper printing, painting with oil paints, and by implanting electronic components (dynamic iris). The oil painting method can produce an aesthetic 3D iris. However, when utilizing heat-cured acrylic resin to integrate the iris into the sclera, the use of a pressing machine when packing can distort the oil paint. Objectivess: The use of UV-resin material for iris fabrication can reduce the risk of distortion, reduce laboratory procedures, and produce an aesthetic iris. Case Report: A 28-year-old male came to Universitas Sumatera Utara dental hospital with complaint of the previous occular prosthesis felt loose and unaesthetic. Patient has been wearing the prosthesis for ±10 years. The patient wants a new occular prosthesis to replace the old prosthesis. Iris coloring is done with painting paper and oil paint, iris button is made with UV-resin using a pre-fabricated mold, then the iris is implanted into the sclera. The use of UV-resin for creating an iris requires only a few basic equipment and materials, has a quick-curing period, and facilitates iris position determination. Conclusion: Fabricating occular prosthetic with iris buttons made from UV-resin reduces the risk of laboratory failure and produces better esthetics.